2000
DOI: 10.1001/archsurg.135.6.657
|View full text |Cite
|
Sign up to set email alerts
|

Cryosurgical Ablation and Radiofrequency Ablation for Unresectable Hepatic Malignant Neoplasms

Abstract: Some say the world will end in fire, Some say in ice. From what I've tasted of desire I hold with those who favor fire. But if it had to perish twice, I think I know enough of hate To know that for destruction ice Is also great And would suffice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
134
2
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(143 citation statements)
references
References 24 publications
2
134
2
3
Order By: Relevance
“…28 It is difficult to compare the results of cryotherapy and radiofrequency ablation because of the lack of standard criteria for defining resectability and the different histologic types reported in most series. One study comparing the two techniques 29 demonstrated that radiofrequency ablation resulted in lower morbidity for tumors less than 3 cm in diameter, but was less effective than cryotherapy for treating larger tumors. In this subgroup of large tumors, cryotherapy involved significantly shorter treatment time and lower rates of complications and local disease recurrence.…”
mentioning
confidence: 99%
“…28 It is difficult to compare the results of cryotherapy and radiofrequency ablation because of the lack of standard criteria for defining resectability and the different histologic types reported in most series. One study comparing the two techniques 29 demonstrated that radiofrequency ablation resulted in lower morbidity for tumors less than 3 cm in diameter, but was less effective than cryotherapy for treating larger tumors. In this subgroup of large tumors, cryotherapy involved significantly shorter treatment time and lower rates of complications and local disease recurrence.…”
mentioning
confidence: 99%
“…3,4 It was a well-designed first randomized trial that reports on these potential benefits, which is consistent with previous nonrandomized studies. 5,6 However, the subgroup analyses are still losing their statistical power owing to the small number of patients, which is sensitively influenced by aberrant cases. Additional information, including baseline characteristics and 1-, 3-, and 5-year progression free survival (adjusted by multivariate regression model, if necessary) for each of the >3 cm HCC patient subgroups would be required to reduce perceived bias.…”
Section: Randomized Controlled Trial Of Percutaneous Cryoablation Vementioning
confidence: 99%
“…3,4 It was a well-designed first randomized trial that reports on these potential benefits, which is consistent with previous nonrandomized studies. 5,6 However, the subgroup analyses are still losing their statistical power owing to the small number of patients, which is sensitively influenced by aberrant cases. Additional information, including baseline characteristics and 1-, 3-, and 5-year progression free survival (adjusted by multivariate regression model, if necessary) for each of the >3 cm HCC patient subgroups would be required to reduce perceived bias.…”
Section: Randomized Controlled Trial Of Percutaneous Cryoablation Vementioning
confidence: 99%